Practical aspects of implementation of marketing technologies in the tourism enterprise: Experimental case of two tourism enterprises from France and Ukraine - Ekouaghe, Matthnai (Technium Social Sciences Journal, 2020)
The function of marketing has always been to connect companies with their audiences in the right place at the right time. Today, you have to meet consumers where they spend most of their time: on the internet, from your company’s website to the various aspects of online branding (digital advertising, e-mail marketing, web brochures). , etc.), digital marketing covers a wide spectrum of tactics and content. For enterprises operating in a market economy such as tourism, the issue of effective marketing activities, which is a system of measures to meet consumer demand for relevant products and services, is highly relevant. A prerequisite for the development of the first direction is that in connection with the introduction of e-commerce and e-business in the practice of firms, corporations and banks, there have also been changes in the nature of commercial and financial transactions, relationships with partners and customers, the development and implementation of business strategies, the formation of competitive advantages. The pusrpose of the article is to demonstrate the practical aspects of implementation of marketing technologies in the tourism enterprise : experimental case of two tourism enterprises from france and ukraine